2017
DOI: 10.1111/jcmm.13275
|View full text |Cite
|
Sign up to set email alerts
|

cPKCγ‐mediated down‐regulation ofUCHL1 alleviates ischaemic neuronal injuries by decreasing autophagyviaERKmTORpathway

Abstract: Stroke is one of the leading causes of death in the world, but its underlying mechanisms remain unclear. Both conventional protein kinase C (cPKC)γ and ubiquitin C‐terminal hydrolase L1 (UCHL1) are neuron‐specific proteins. In the models of 1‐hr middle cerebral artery occlusion (MCAO)/24‐hr reperfusion in mice and 1‐hr oxygen–glucose deprivation (OGD)/24‐hr reoxygenation in cortical neurons, we found that cPKCγ gene knockout remarkably aggravated ischaemic injuries and simultaneously increased the levels of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Whether autophagy is beneficial or detrimental depends upon the extent of autophagy induction and the duration of autophagy activation (36). Administration of 3-MA or Baf A1 largely protected them from cell death in primary cultured cortical neurons and significantly reduced MCAO/R-induced brain infarct volume, brain edema and motor deficits, suggesting autophagy contributes to cell death both in vitro and in vivo (16,17,37). In line with this, our results showed that autophagy was induced in OGD/R-treated neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether autophagy is beneficial or detrimental depends upon the extent of autophagy induction and the duration of autophagy activation (36). Administration of 3-MA or Baf A1 largely protected them from cell death in primary cultured cortical neurons and significantly reduced MCAO/R-induced brain infarct volume, brain edema and motor deficits, suggesting autophagy contributes to cell death both in vitro and in vivo (16,17,37). In line with this, our results showed that autophagy was induced in OGD/R-treated neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of autophagy was witnessed in neurons after oxygen-glucose deprivation (OGD)/reoxygenation (R) and MCAO/R treatments (15)(16)(17). However, the role of autophagy and IL-17A in ischemic stroke are still ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional PKCγ reduces neuron-specific autophagy via phosphorylation of mTOR on serine 2448 and serine 2481 [92]. It has been reported that cPKCγ provokes the inhibition of ubiquitin C-terminal hydrolase L1 (UCHL1) and is involved in the ERK-mTOR mediated autophagy during ischemic neural injury [93].…”
Section: Pkc In Autophagy Mechanismmentioning
confidence: 99%
“…mTOR controls cell survival under growth-promoting factors and it has the ability to phosphorylate cPKC and Akt in order to establish protein stability [151]. The inhibition of ubiquitin C-terminal hydrolase L1 (UCHL1) by cPKCγ restricts autophagy through the activation of ERK-mTOR pathway and reduces ischemic neural injury [93].…”
Section: Roles Of Pkc Isozymes In Neurodegenerative Disease Progressimentioning
confidence: 99%
“…24 Circulating UCH-L1 has been identified as a biomarker specific to neuronal injury 16,25 as it is released into the circulation when the integrity of the blood-brain barrier (BBB) is disrupted. 26,27 In a piglet model, serum UCH-L1 predicted neuronal apoptosis induced by deep hypothermic circulatory arrest. 28 In observational studies, cerebrospinal fluid (CSF) and serum levels of UCH-L1 had utility as diagnostic and prognostic biomarkers of traumatic brain injury.…”
Section: Baseline Characteristics Of the Study Patientsmentioning
confidence: 99%